Is There a Relationship Between Patient-Reported Satisfaction and Persistence on Overactive Bladder Syndrome Pharmacotherapy?. Issue 3 (May 2018) - Tran, Alexis M.; Reis, Renata; Iyer, Shilpa; Botros, Carolyn; Goldberg, Roger P.; Sand, Peter K.; Botros, Sylvia M.
Abstract : Objectives: This study aimed to determine the relationship between patient satisfaction with overactive bladder syndrome (OAB) pharmacotherapy and persistence rates. We compared persistence rates between satisfied and dissatisfied patients at designated study intervals. Methods: This was a retrospective cohort study of new patients who initiated OAB medication. Patients were classified as either satisfied or dissatisfied on the basis of a single-item treatment satisfaction question. Persistence was defined as continuous days on therapy. The measured rate of persistence was determined as the ratio of patients who persisted on medication at 4, 12, and 24 weeks. Data collection included demographic and prescription information; urinary symptom parameters, symptom and quality-of-life scales, and patient-reported outcomes. Two-sample t test or Wilcoxon rank sum test was used to compare continuous outcomes between both groups (satisfied vs not satisfied). χ 2 Test or Fisher exact test was used to compare categorical outcomes between groups. Results: We analyzed the first 116 charts that met our inclusion criteria. Satisfied and dissatisfied patients did not differ in demographic variables. Satisfied patients had a median of 461 vs 254 persistent days ( P = 0.0001). Satisfied patients (12.5% vs 40%) were less likely to discontinue medication ( P = 0.0068). The discontinuation-free distribution was significantly different between satisfied and dissatisfied cohorts, favoring those who reported satisfaction with OAB medication at all time points ( P < 0.0001). Patients who totally discontinued pharmacotherapy were 7 times more likely to be dissatisfied (odds ratio, 7.0; P = 0.002). Conclusions: Our study helps clarify the relationship between persistence on OAB medication and treatment satisfaction. We found that persistence could serve as a surrogate marker for patient satisfaction because those who reported being satisfied were more likely to persist on therapy at all study intervals. Abstract : Patient persistence on OAB pharmacotherapy relates to patient satisfaction.